2014
DOI: 10.2147/dmso.s40036
|View full text |Cite
|
Sign up to set email alerts
|

Partnering with diabetes educators to improve patient outcomes

Abstract: Diabetes is a chronic, progressive disease that affects millions worldwide. The paradigm of diabetes management has shifted to focus on empowering the person with diabetes to manage the disease successfully and to improve their quality of life. Diabetes self-management education is a collaborative process through which people with diabetes gain the knowledge and skills needed to modify their behavior and to self-manage successfully the disease and its related conditions. Diabetes educators are health care prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 72 publications
(68 reference statements)
0
86
0
4
Order By: Relevance
“…12 Interviews were conducted in a private and quiet place based on the participants’ choice. All the participants signed the consent informed form.…”
Section: Methodsmentioning
confidence: 99%
“…12 Interviews were conducted in a private and quiet place based on the participants’ choice. All the participants signed the consent informed form.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, measures of patients' self-effi cacy and literacy may be useful in selecting and developing appropriate educational approaches and partnerships (such as with diabetic educators) [ 76 ].…”
Section: Individualized Guidelines For Wellness Managementmentioning
confidence: 99%
“…This situation places increasingly greater emphasis on patient education and shared decision-making about medication benefits and risks, lifestyle modifications including diet and exercise, and self-care practices. [3] Background Approximately 28 million people in the U.S, or 9% of the population, have type 2 diabetes and are at risk of, or affected by, related complications including heart disease, retinopathy, nephropathy, and neuropathy. [4] Direct and indirect costs of diabetes in the U.S. are estimated to total $245 billion.…”
Section: Problemmentioning
confidence: 99%
“…[5] Gaps are especially evident for racial and ethnic minorities, groups that account for a large proportion of people with diabetes in the U.S. [5][6][7][8] From a patient-centered perspective, important factors that contribute to suboptimal diabetes care include ineffective communication between health care professionals and their patients, and shortcomings in provision of patient education and counseling about medications and lifestyle. [3,9] Gaps in compliance with these types of patient-centered quality measures were recently reported by researchers who analysed the medical records of 27,225 patients with diabetes and 584,587 encounters with their primary care providers. [10] Only 40% of the patients' records indicated that providers offered lifestyle counseling, and only 10% documented medication intensification, which reflects a lack of communication and shared decision-making about appropriate therapy changes.…”
Section: Problemmentioning
confidence: 99%